IMPROVEMENT OF QUALITY MANAGEMENT SYSTEM IN THE ENTERPRISE – CASE STUDY - Anatolii ZADOIA; Małgorzata GÓRKA; Bogusław ŚLUSARCZYK; Agnieszka WOŹNIAK; Aneta KASPERKIEWICZ (Humanities and Social Sciences)
The article presents the improvement of the quality management system through the example of a selected manufacturing enterprise. Lean Management tools were applied, showing how the development of the enterprise is affected when using appropriate methods, tools, principles, and techniques of quality management. The article presents various stages of the 5S method, which was aimed at maintaining order and discipline at workstations through the development of appropriate habits by employees. In addition, a questionnaire was used to determine the knowledge and attitude of employees concerning the operation of the solutions introduced in the enterprise studied. The research presented in the article shows how it is possible to strive for a significant improvement in quality in the operation of a manufacturing enterprise without the involvement of financial resources.